PENGARUH KUALITAS LAYANAN, HARGA, KEPERCAYAAN, KEPUASAN, DAN PROMOSI TERHADAP KEPUTUSAN MENGGUNAKAN SHOPEE FOOD - Petra Surya Mega Surya Mega; Mr Hardono; Nerys Lourensius L Tarigan; Thomas Aquinas Radito; Kristian Feliks Kodora (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2022)
Competition between online service managers is getting more challenging by providing several uniqueness to the products offered so that consumers are interested in purchasing or using the goods presented. One online company that is quite aggressive is Shopee Food. Consumers today are straightforward to find on the uniform road of Shopee Food drivers on duty or waiting to enter orders. The objectives of this research include testing the influence of service quality, price, trust, satisfaction, and promotion on the decision to use Shopee Food. The sample of this study was 100 people who became Shopee Food customers where they live in Yogyakarta. The results of the respondent's answers will be used to test the constructed hypothesis. The sampling technique uses convenience sampling. The data show that price, satisfaction, and promotion significantly influence buying Shopee Food. At the same time, service quality and trust variables are relatively independent of the decision to use Shopee Food.